2022
DOI: 10.3847/1538-4357/ac4e8f
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Observations of Molecular Complexity in the Large Magellanic Cloud: The N 105 Star-forming Region

Abstract: The Large Magellanic Cloud (LMC) is the nearest laboratory for detailed studies on the formation and survival of complex organic molecules (COMs), including biologically important ones, in low-metallicity environments—typical of earlier cosmological epochs. We report the results of 1.2 mm continuum and molecular line observations of three fields in the star-forming region N 105 with the Atacama Large Millimeter/submillimeter Array. N 105 lies at the western edge of the LMC bar with ongoing star formation trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 179 publications
(299 reference statements)
2
36
0
Order By: Relevance
“…Figure 2 shows selected frequency ranges of the ALMA Band 6 spectra of hot cores N 105-2 A and B, covering the HDO 241.6 GHz line, as well as the methanol (CH 3 OH) J = 5-4 Q-branch at ∼241.8 GHz and the methyl cyanide (CH 3 CN) 14 K -13 K ladder for reference. The molecular line identification and spectral modeling for all spectral windows were performed for all the continuum sources in N 105-2 in Sewiło et al (2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 shows selected frequency ranges of the ALMA Band 6 spectra of hot cores N 105-2 A and B, covering the HDO 241.6 GHz line, as well as the methanol (CH 3 OH) J = 5-4 Q-branch at ∼241.8 GHz and the methyl cyanide (CH 3 CN) 14 K -13 K ladder for reference. The molecular line identification and spectral modeling for all spectral windows were performed for all the continuum sources in N 105-2 in Sewiło et al (2022).…”
Section: Resultsmentioning
confidence: 99%
“…We detected the HDO 2 11 -2 12 line at 241.5616 GHz with ALMA toward hot cores N 105-2 A and N 105-2 B in the starforming region N 105 in the Large Magellanic Cloud (LMC; briefly reported in Sewiło et al 2022). These are two out of only a handful of known bona fide extragalactic hot cores, all located in the LMC (Shimonishi et al 2016b(Shimonishi et al , 2020Sewiło et al 2018Sewiło et al , 2019Sewiło et al , 2022 The LMC, an irregular dwarf galaxy, is the most massive and one of the nearest (50.0 ± 1.1 kpc; Pietrzyński et al 2013) satellites of the Milky Way.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…This indicates that, even at metallicities lower than the Solar one, planets capable to host life can be found, depending also on the dynamical history of the planet host stars (Dai et al 2021), which is likely to be different in the inner and outer Galaxy. Second, observations performed with the Atacama Large Millimeter Array (ALMA) towards the Large and Small Magellanic Clouds (LMC and SMC, Shimonishi et al 2018, Sewiło et al 2018, Sewiło et al 2022, two external galaxies having metallicity ∼ 3 and ∼ 5 times lower than Solar, respectively, have detected emission of complex organic molecules (COMs), which are organic species with more than five atoms. This finding, and the recent discovery of a hot molecular core rich in COMs at GC of ∼ 19 kpc (Shimonishi et al 2021), have clearly suggested that the astrochemical processes that can lead to species of pre-biotic interest can be found also in metal poor environments.…”
Section: Introductionmentioning
confidence: 99%